The CSR program of PT Kalbe Farma Tbk in Providing Clean Water in Wonogiri, Central Java - Gan Gan Giantika (PT ARRUS Intelektual Indonesia, 2024)
The CSR program of PT Kalbe Farma Tbk, which provides clean water to Wonogiri in Central Java, has been running since 2013. Clean water is a basic human need and crucial for health and community welfare, daily activities, and productivity. Therefore, efforts are needed to meet the clean water needs of the community in Wonogiri, Central Java. This CSR program focuses on the sustainability of the health sector by considering economic, environmental, and health aspects, as well as social and administrative aspects (ESG). This research aims to understand how the CSR program of PT Kalbe Farma Tbk is implemented to provide clean water in Wonogiri, Central Java. In this study, the researcher used a qualitative approach and a case study as a research method to explain the implementation of the program. The provision of clean water by PT Kalbe Farma Tbk has proven to improve the surrounding community's welfare, health, and economic development. PT Kalbe Farma Tbk implements CSR programs as a sustainability initiative in the health sector, considering economic, environmental, social, and governance aspects (ESG).